2014
DOI: 10.4028/www.scientific.net/msf.805.632
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 4A-Zeolite for Adsorption of CO<sub>2</sub>

Abstract: The gas separation is a very expensive step in the chemical industry and unquestionable relevance. In this work, was verified the efficiency of the use of type A-zeolites in the separation of CO2 in a gas mixture containing 25% CO2, 4% O2 and 71% N2. These concentrations are similar to the effluent gases from combustion processes. To this end, was synthesized type A-zeolites using commercial kaolin and mounted to an adsorption column to test the effectiveness of zeolites in the adsorption of CO2. The synthesiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Authors observed an increase of the surface area, with a maximum S BET value of 876 m 2 /g, being highly microporous in all cases, which provides excellent properties as a molecular sieve to capture CO 2 , obtaining an adsorption close to 211 mg CO 2 /g at 25 • C and under 1 bar [58]. In the same way, clay minerals have also been used as starting materials to synthesize zeolites type A from kaolinite, obtaining a CO 2 adsorption capacity of 0.46 mg CO 2 /g zeolite after only 77 s [60]. Pour et al (2016) [61] also synthesized A-zeolite, using a montmorillonite as a starting clay, reaching an excellent CO 2 adsorption of about 220 mg CO 2 /g, with a high selectivity in mixtures of CO 2 /CH 4 at 1 bar of pressure, although an increase of the pressure causes a decrease of the selective adsorption.…”
Section: Co 2 Adsorption Of Materials Synthesized From Clay Mineralsmentioning
confidence: 99%
“…Authors observed an increase of the surface area, with a maximum S BET value of 876 m 2 /g, being highly microporous in all cases, which provides excellent properties as a molecular sieve to capture CO 2 , obtaining an adsorption close to 211 mg CO 2 /g at 25 • C and under 1 bar [58]. In the same way, clay minerals have also been used as starting materials to synthesize zeolites type A from kaolinite, obtaining a CO 2 adsorption capacity of 0.46 mg CO 2 /g zeolite after only 77 s [60]. Pour et al (2016) [61] also synthesized A-zeolite, using a montmorillonite as a starting clay, reaching an excellent CO 2 adsorption of about 220 mg CO 2 /g, with a high selectivity in mixtures of CO 2 /CH 4 at 1 bar of pressure, although an increase of the pressure causes a decrease of the selective adsorption.…”
Section: Co 2 Adsorption Of Materials Synthesized From Clay Mineralsmentioning
confidence: 99%
“…For zeolite 4A and amine-modified Zeolites, the positions of characteristic peaks are consistent, the same as based 4A-zeolite. The most intense peaks occur at 17.2°, 26.17°, 35.1°, 40.2°, and 60° 2θ, which can be indexed to an amorphous structure consistent with zeolite 4A because it was synthesized from clay materials 65 . All zeolites exhibit additional peaks when compared to the untreated 4A-zeolite.…”
Section: Resultsmentioning
confidence: 98%
“…The commonly used techniques for CO 2 separation include cryogenic distillation, absorption, membrane separation, and an adsorption process. , As a very popular and promising method for separating and capturing CO 2 , the adsorption process possesses distinguished adsorbents with low operation requirements, low energy consumption, low capital investment, and high efficiency to adsorb CO 2 . In the process of CO 2 adsorption, it is crucial to choose an efficient adsorbent for the high adsorption and regenerability . In general, a good CO 2 adsorbent features large adsorption capacity, stability (thermal, mechanical, and chemical), and regenerability. , Currently, activated carbon, zeolites (13X, 4A), , and silica gel have been widely used for CO 2 capture. Compared to zeolites, activated carbon with a large adsorption capacity is not suitable for gas separation in engineering because of its poor adsorption selectivity to mixed gases and lower CO 2 adsorption capacity at low pressures (<173 kPa). , …”
Section: Introductionmentioning
confidence: 99%